The The Determinants of The Successfully Completing Primary Immunization Program in Empat Lawang Regency South Sumatera - Alexsander; Budiman Sakti; Cerianti; Henny Aprianty; Dodo Sutardi; Harmiati (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
This study aims to explain the complete primary immunization (Y) and how much the determinants of health infrastructure factors (X1), health budget support (X2), quality of vaccines and equipment (X3), and implementing personnel (X4), Partially and simultaneously, affect Y. The method used is explanatory quantitative. The study locates at the Pendopo Barat and Talang Padang Community Health Centers with a sample of 48 people (5%) based on proportionate stratified random sampling. The results reveal that (1) Partially, X1 affected Y, with r-count X1Y(2.731); X2 had no effect on Y, with r-count X2Y(1.435); X3 had no affected Y, with r-count X3Y(0.380); X4 affected Y, with r-count X4Y(3.322), (2) Simultaneously, the variables X1, X2, X3, and X4 affected Y, with F-count value(6.029). The research implies an urgent calibration for the equipment, besides the need to increase the quantity of immunization equipment.